2020
DOI: 10.3389/fpsyg.2020.00417
|View full text |Cite
|
Sign up to set email alerts
|

A World Unto Itself: Human Communication as Active Inference

Abstract: Human Communication as Active Inference "The point we emphasize is strong confidence in our original nature, " Suzuki (1970/2014, p. 35) 1 Crucial to our account, in the active inference formulation 'beliefs' refer to (subpersonal) Bayesian beliefs-in the sense of Bayesian belief updating or belief propagation (as opposed to propositional beliefs). 2 On a deflationary view, this is the only solution that can exist, in terms of minimizing the surprise or free energy of coupled free energy minimizing agents. See… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 316 publications
(512 reference statements)
1
107
0
Order By: Relevance
“…Shared expectations, selective patterning of attention and behavior, cultural evolution, the formation of joint goals, implicit learning, and cultural inheritance underpin an active inference account of cognition [124]. Humans are predisposed to align their mental states with others of the same kind, and human communication can largely be cast as a cooperative activity that serves to reduce uncertainty [178]. In the process, communication and the culture that it spawns offloads some of the computational demand that an individual would otherwise face onto the larger cultural (and physical) niche.…”
Section: Self-similarity Cooperation Cognition and Communicationmentioning
confidence: 99%
“…Shared expectations, selective patterning of attention and behavior, cultural evolution, the formation of joint goals, implicit learning, and cultural inheritance underpin an active inference account of cognition [124]. Humans are predisposed to align their mental states with others of the same kind, and human communication can largely be cast as a cooperative activity that serves to reduce uncertainty [178]. In the process, communication and the culture that it spawns offloads some of the computational demand that an individual would otherwise face onto the larger cultural (and physical) niche.…”
Section: Self-similarity Cooperation Cognition and Communicationmentioning
confidence: 99%
“…Generative models are at the heart of things like the free energy principle and dynamic causal modelling (Friston, Moran, and Seth 2013;Friston 2019), in the sense that these approaches to 'sense-making' rest on model evidence: a function (i.e., marginal likelihood) of some data, under probabilistic beliefs about how those data were caused; i.e., a generative model. For example, dynamic causal modelling-originally developed in computational neuroscience (Friston 2019)-is gaining prominence in several other fields, such as cognitive and social psychology (e.g., Vasil et al 2020) and epidemiology (e.g., Friston et al 2020).…”
Section: Generative Modellingmentioning
confidence: 99%
“…Consequently, it has been suggested that the variational free energy of a system's sensory states is a measure of how well the system fits its niche. Since other systems are also part of the environment, social interaction can also be seen as Active Inference, including communication (Vasil, Badcock, Constant, Friston & Ramstead, 2020) and mental alignment (Friston & Frith, 2015;Ramstead, Veissière & Kirmayer, 2016) on a fast scale and formation of norms as a kind of social niche construction on longer timescales (Veissière, Constant, Ramstead, Friston, & Kirmayer, 2019).…”
Section: The Free Energy Principlementioning
confidence: 99%